2021
DOI: 10.1038/s41598-021-97884-2
|View full text |Cite
|
Sign up to set email alerts
|

Confidence guides priority between forthcoming tasks

Abstract: Humans can estimate confidence in their decisions, and there is increasing interest on how this feeling of confidence regulates future behavior. Here, we investigate whether confidence in a perceptual task affects prioritizing future trials of that task, independently of task performance. To do so, we experimentally dissociated confidence from performance. Participants judged whether an array of differently colored circles was closer to blue or red, and we manipulated the mean and variability of the circles’ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Metacognition can be considered as the awareness or subjective evaluation one can make of cognitive processes such as perception (e.g., Dunlosky & Metcalfe, 2008; Metcalfe & Shimamura, 1994; Nelson & Narens, 1994). For example, confidence is a metacognitive level that has been shown to regulate different aspects related to visual decision making (for reviews see Mamassian, 2016, 2020) such as whether one needs to accumulate further evidence to make a decision (Balsdon et al, 2020) or even regulate behavior acting as a priority signal (Aguilar-Lleyda et al, 2020; Aguilar-Lleyda & de Gardelle, 2021). It is thus a possibility that being able to access information of how well one discriminates the objects’ movements has influenced the criteria set to decide to go leading to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognition can be considered as the awareness or subjective evaluation one can make of cognitive processes such as perception (e.g., Dunlosky & Metcalfe, 2008; Metcalfe & Shimamura, 1994; Nelson & Narens, 1994). For example, confidence is a metacognitive level that has been shown to regulate different aspects related to visual decision making (for reviews see Mamassian, 2016, 2020) such as whether one needs to accumulate further evidence to make a decision (Balsdon et al, 2020) or even regulate behavior acting as a priority signal (Aguilar-Lleyda et al, 2020; Aguilar-Lleyda & de Gardelle, 2021). It is thus a possibility that being able to access information of how well one discriminates the objects’ movements has influenced the criteria set to decide to go leading to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, starting with an easy task can ensure early task achievement (Fournier, Coder, et al, 2019). Additionally, prioritizing tasks more confidently can reduce the extra cognitive load before performing a difficult task (Aguilar‐Lleyda & de Gardelle, 2021). People can spend more time on a difficult task by starting with an easy one to reduce the cognitive load.…”
Section: Diversification Of Procrastinationmentioning
confidence: 99%
“…These findings, however, remain inconclusive. When there are multiple tasks of varying difficulty, some studies advocate starting with simpler tasks to minimize cognitive load and facilitate earlier accomplishments (Fournier, Coder et al, 2019) and that prioritizing tasks with more confidence can reduce cognitive load before undertaking complex tasks (Aguilar-Lleyda & de Gardelle, 2021). Other studies have indicated that commencing with a demanding task first decreases self-efficacy (Weinstein & Roediger, 2010).…”
Section: Task Order Based On the Type Of Taskmentioning
confidence: 99%